Student Perspectives While Serving Asylum Seekers: A Pilot Study - Hanna, Kristiana; Dasani, Divya; Jayapal, Aishwarrya; Shah, Sapan; Adam, Octavian (Journal of Student-Run Clinics, 2023)
Background: Medical student-run asylum clinics, which support asylum seekers with medical/psychological evaluations provided by asylum clinics, have significantly expanded in the United States in the last ten years, but minimal data reviews the impact of a program like this on the professional development of providers and students. This study analyzes how student participation impacts cultural competency and professional adeptness. Methods: Fifty-eight CDAC (n=26) and non-CDAC (n=32) participants were surveyed on demographics, comfort, and experiences interacting with asylum populations, as well as philanthropic characteristics of altruism, empathy, and compassion. Data collection and analysis were conducted using Qualtrics, R, and non-parametric testing (Mann Whitney U test, Fisher’s exact test). Results: Those who participated in CDAC endorsed greater overall experience interacting with asylum populations (p=0.01), particularly serving refugee populations (p=0.004) and having difficult conversations about physical and mental trauma (p=0.02). CDAC participants also scored higher on select measures of altruism and empathy. Conclusion: Participation in service-learning programs is important to medical education and practice, particularly in primary care. CDAC offers a unique learning opportunity for clinicians to gain cultural competency skills while providing vital assistance to marginalized populations, even for those with no prior formal training.